Improving buckling and post-buckling of shape memory alloy laminated composite plates subjected to mechanical and thermal loading using finite element method - A.Rasid, Zainudin (2012)
This research work focuses on simulation work involving development of finite element formulations and its finite element based software validated against experimental results reported in the literature to subsequently facilitate parametric studies. Nitinol shape memory alloy with its well-known property of the shape memory effect is used to improve post-buckling of laminated composite plates subjected to mechanical, thermal and thermo-mechanical loadings. Two finite element formulations for the postbuckling of composite plates with embedded shape memory alloy, namely the total strain and the incremental strain formulations are used. Both formulations are derived based on the first order shear deformation theory while the strength of material approach is used to include the effect of recovery stress in the constitutive equation. Thermal loading can be uniform or non-uniform throughout the width and thickness of the composite plates. The properties and recovery stress of the nitinol are either determined by solving the Brinson’s model or taken from experimental data of others. The formulations were solved using the Newton-Raphson’s method and source codes were developed for this purpose. Parametric studies were conducted theoretically to investigate the effects of the shape memory alloy on the post-buckling behaviour of composite plates with regard to several composite related and shapememory alloy related parameters. The addition of shape memory alloy wires within layers of composite plates has resulted in the significant improvement in the composite critical loads. In the case of simply supported boundary condition, the increase of the critical load can be up to 70% for the shape memory alloy layer thickness equal to one fourth of the total thickness of other layers. The post-buckling paths of the composite plates subjected to mechanical, thermal and thermo-mechanical loadings are stable and substantially improved after the addition of the shape memory alloy. For the four types of configurations under studied here, the improvement of the active strain energy tuning method is at the highest in the case of the symmetric angle-ply plate where bifurcation for this plate occurs at the ratio of the load over critical load of P/Pcr=3. It is interesting also to see that while the test mechanical post-buckling paths occur if the shape memory alloy layer is located in the middle of the plate, the location of the shape memory alloy layers has no effect on the thermal post-buckling paths. In the case of the tent-like temperature of the distribution, the non-uniform temperature distribution where the ratio of the temperature of the uniform temperature rise part to the temperature gradient. T1/To=l has allowed the post-buckling response to occur earlier compared to the case of To=O loading. At the same time for both cases of the active property tuning and the active strain energy tuning, the post-buckling paths are improved with the increase of the ratio Tl/To. Furthermore the thermal post-buckling paths that are degraded initially due to the compressive loading are shown to jump upward significantly with the addition of the shape memory alloy. At the end this research has shown that the developed model and the source codes are able not only to show the significant improvement made by the shape memory alloy on the post-buckling behaviour of composite plates subjected to mechanical themal and themo-mechanical loadings but also to demonstrate the post-buckling behaviour of the shape memory alloy composite plates subjected to several parameter changes.